Powder Flowability in Snack Food Coatings, Insights from Rheometric and Morphological Analysis - Nyangena, Chelsea (My University, 2025)
The rheological characteristics of powders are crucial in the food industry, affecting production and prod uct quality. This research conducted at Santa Maria AB focused on the characteristics of cheese-based snack seasoning powders’ flow properties under varying formulations and environmental conditions, utilizing both rheometric and morphological assessments. It investigated silicon dioxide’s impact on flowability, compared rheological traits of in-house and external suppliers’ samples, assessed humidity and storage effects on flowa bility, and assessed morphological data of five samples. Supplementary methods such as particle sieve analysis and water activity testing were also employed for enhanced interpretation of powder behavior. Rheometric assessments utilized the FT4 powder rheometer® by Freeman Technology, while morphological evaluations were conducted by the Danish Technical Institute. Key findings revealed that added silicon dioxide (SiO) improved flowability, agreeing with existing litera ture. In-house samples in the aeration test exhibited rheological similarities to external supplier samples when SiO was included.However, original in-house samples with 1.3% SiO (SM-1.3%) had lower cohesion values than external samples. This suggests that shear resistance alone does not capture the flow behavior of the seasoning but also there is a possible interplay between cohesion and adhesion. Furthermore, PCA plot of the collected data from the FT4 powder rheometer® displayed no apparent clustering among the samples but rather indicated that differences in rheological behavior could be attributed to factors that were not captured in the rheometric assessment. From the morphological assessment, findings revealed that the sample SM-1.3% was larger than SM-1.75% in terms of diameter, further strengthening the observed effect of silicon dioxide on flowability. Sample with higher silicon dioxide tended to have smaller and more spherical particles but also a narrow particle size distribution. In addition, humidity testing confirmed the impact of SiO2 on flowability where samples subjected to higher relative humidity displayed more cohesive behavior, aligning with previous research. Lastly high shear mixers on fine powders increased cohesion and aerated energy, without improving flowability. No significant particle size distribution differences were found between low and high shear mixing, however, further replicates could provide statistical robustness. Conclusively, results emphasized the importance of anti-caking agents such as silicon dioxide, environmental control, and the use of appropriate mixing methods for optimizing powder flow. These findings provide a framework for improving seasoning performance in industrial applications. Future research could benefit from added replicates, visual inspection such as image analysis and the influence of fat content on powder behavior to determine the influence of ingredient selection
Keywords: Powder rheology, flowability, food powder, FT4 powder rheometer®, particle morphology, mixing intensity, snack seasoning, anti-caking agents, humidity effects, adhesion